Budd-Chiari Syndrome - classification, diagnostics, imaging and treatment - Agnieszka Rybkowska; Magda Żuchnik; Gabriela Licak; Paulina Bętkowska; Jakub Radulski; Michał Paluch; Michał Tomkiewicz; Julia Tomkiewicz; Piotr Sałata; Paulina Szczuraszek (Nicolaus Copernicus University in Toruń, 2023)
Introduction: Budd-Chiari syndrome is a rare condition which can be defined as hepatic venous outflow obstruction occurring at any level between the small hepatic veins and junction of the inferior vena cava and the right atrium. Symptoms may vary from mild or even asymptomatic for many years to fulminant hepatic failure. Imaging is the mainstay of diagnosis of BCS. Laboratory and ematological tests are invaluable in recognizing hematological and coagulation disorders that may be identified in up to 75% of the patients. The recommended therapeutic approach to BCS is based on a stepwise algorithm beginning with medical treatment, endovascular treatment to restore vessel patency, placement of transjugular portosystemic shunt (TIPS), and orthotopic liver transplantation as a last resort rescue treatment. The aim of the study: This study aims to gather current knowledge about clinical manifestations, diagnosis and treatment of Budd-Chiari syndrome. Materials and methods: This review was based on available data collected in the PubMed database and Google Scholar web search engine, using the keywords: 'Budd-Chiari syndrome' ,'hepatic venous outflow obstruction'. Conclusions: The treatment of Budd-Chiari syndrome requires interdisciplinary cooperation, which has resulted in the increasing curability of this rare disease over the last years.